Individuals and Information Overload in Organizations: Is More Necessarily Better? - O'Reilly, C. A. (Academy of Management Journal, 1980)
Hypotheses were postulated that perceived information overload would be associated with higher satisfaction and lower performance of decision makers than would perceived information underload. The ...